Consequências da exposição intra-uterina ao agonista canabinóide WIN 55,212-2: impacto sobre o sistema cardiorrespiratório e ciclo sono-vigília durante o desenvolvimento em ratos - Patrone, Luis Gustavo Alexandre (Universidade Federal de São Carlos, 2021)
Policies for the flexibility and legalization of Cannabis use in several countries has increased considerably in recent years and the use of drugs of abuse during pregnancy can affect the development of physiological systems including the respiratory control network, mainly due to the susceptibility of the prenatal period to external and pharmacological interventions resulting in possible consequences in the offspring’s postnatal life. Cannabis psychoactive compounds can act directly on the endocannabinoid system present in the Central Nervous System (CNS) already in the early stages of embryonic development, being an important element for structural and functional regulation of CNS maturation, including for the areas responsible for cardiorespiratory control. However, despite the increased consumption of this substance during pregnancy, knowledge about the influence of exogenous cannabinoids on the development of the respiratory system and the consequences on postnatal life is limited. The present study evaluated the possible effects of cannabinoid receptor (CB) agonist exposure during pregnancy on the respiratory control system of neonatal (P0, P6-7 and P12-13), juvenil (P27-28) and adult (P80-81) male and female rats through subcutaneous implantation of osmotic pumps in pregnant female rats at embryonic day 0 and delivered vehicle or agonist (WIN 55212-2, 0.5 mg/kg/day) for 21 days. WIN exposure interfered in a sex-specific maner with breathing regulation of offspring, thereby promoting a greater sensitivity to CO2 in neonatal, juvenile and adult males. An altered chemoreflex in response to hypoxia was observed in P0 and P6-7 newborn males. In females, prenatal treatment resulted only in a hyperventilation during hypercapnia at juvenile age and a reduced ventilatory response to CO2 and O2 at adulthood. In addition, brainstem neuroanatomical analysis showed an increase in the number of catecholaminergic neurons and CB1 receptor expression and alteration of tissue respiration in early stages of males. A significant reduction in lung compliance was also observed in treated juvenile males. Finally, cardiovascular changes were also observed for male and female animals in adulthood due to prenatal WIN exposure. These findings demonstrate that exposure to the cannabinoid receptor agonist during pregnancy results in prolonged and sex-dependent consequences for the cardiorespiratory control system.
Consequences of intrauterine exposure to cannabinoid agonist WIN 55,212-2: impact on the cardiorespiratory system and sleep-wake cycle during development in rats
Keywords: Desenvolvimento; Controle ventilatório; Canabinóides; Quimiossensibilidade; Development; Breathing control; Cannabinoids; Chemosensitivity; CIENCIAS BIOLOGICAS::FISIOLOGIA